Factors Affecting participation in a Diagnostic Examination in Colorectal Cancer Screening using Fecal Occult Blood Testing - MATSUMOTO, Takahiro; TANI, Tomoko; TATSUMI, Yoshihide; NISHIDA, Hiroshi; HARADA, Akiko (Journal of Gastroenterological Mass Survey, 2004)
The relationships between compliance with fecal occult blood testing (FOBT), the number of participants in FOBT, positive rate of FOBT, history of a diagnostic examination after FOBT, and compliance with the diagnostic examination were studied in a worksite setting using a database containing individual data from a mass screening and other health care checks. The subjects were 2, 421 males and 210 females with positive FOBT between 2000 and 2002. Of these, 1,816 males (75.0%) and 144 females (68.6%) underwent diagnostic examinations. A logistic regression analysis was used to investigate the relationships between the factors. In the model, follow-up with a diagnostic examination was denoted as the dependent variable, with the other factors as independent variables. The variables in the analysis were standardized to compare the magnitude of each variable; factors with large negative values were considered the most important in limiting follow-up diagnostic examination. A need for frequent diagnostic examinations and a high rate of positive tests were factors that caused FOBT participants to refrain from having the diagnostic examination. Compliance with FOBT was the only positive relationship with statistical significance. A high positive FOBT rate could impair the reliability of mass screening. To address this problem, FOBT kits should be re-evaluated, and the scheme used for mass screening of individuals who undergo frequent diagnostic examinations but whose results are normal should be improved.